An exploratory analysis of continuing professional development perspectives of Turkish architects according to career stages. (2nd September 2016) - Yalçınkaya Çalışkan, Fadime; Acar, Emrah
ABSTRACT: Continuing professional development (CPD) can be more successful if professional learning is matched with current knowledge, goals and career stages of architects. This is because a distinct set of motivations, drivers and barriers come into play in each career stage. CPD for architects in Turkey is not structured to address the diverse needs of professionals throughout their career life cycle. This study reports the findings of a descriptive–exploratory research which aimed to explore the CPD-related perceptions of the architects who are in their early, mid- and late-career stages. Data from an opinion survey of 120 architects, following a convenience sampling process, were analyzed both statistically and qualitatively. Outputs of the analyses of variance, multiple regression analyses and content analyses of qualitative data suggest that there are differences between the CPD perceptions and orientations of early, mid- and late-career architects according to their demographic characteristics, such as age, gender, marital status and job experience. Findings appear consistent with the socioemotional selectivity theory of psychology, which asserts that individuals tend to prioritize short-term over long-term goals; and pursue less new information when they become aware of their limited time perspective. Findings support the role of contextual factors on learning, such as the traditional role of project delivery processes, informal relationships with colleagues and the problem-based nature of professional learning in architecture. Establishing a stronger link between individual and organizational motivations for CPD is likely to result in more successful policies. Designers of CPD training programs can benefit from the outputs of this research.